HERMENEUTIKA SEBAGAI METODE BARU DALAM MENAFSIRKAN ALQURAN - Mulizar Mulizar (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2017)
This article will discuss hermeneutics as a new method of interpreting the Qur'an.The use of hermeneutics is a new thingin the world of interpretation. Some support and some reject it.The results of this study show that the use of hermeneutics in interpreting the Qur’an must be careful.In addition, This science should be placed as a complement, not as a subdivision of the science of interpretation. On the other hand, hermeneutics paves the way to contextualize the scriptures, so that they can dialogue in different spaces and times, as apologically desirable and held by many religious groups to their respective scriptures.